2017
DOI: 10.3847/1538-4357/aa63f8
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of Starless Core Substructure in Ophiuchus

Abstract: Compact substructure is expected to arise in a starless core as mass becomes concentrated in the central region likely to form a protostar. Additionally, multiple peaks may form if fragmentation occurs. We present Atacama Large Millimeter/submillimeter Array (ALMA) Cycle 2 observations of 60 starless and protostellar cores in the Ophiuchus molecular cloud. We detect eight compact substructures which are 15 >  from the nearest Spitzer young stellar object. Only one of these has strong evidence for being truly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 64 publications
4
68
2
Order By: Relevance
“…The uncertainties correspond to the fit uncertainties only. The fluxes measured at 4.5 and 7.5 GHz come from Dzib et al (2013), while the ones at 107 GHz come from Kirk et al (2017). It should be noted that the The brightest source in our sample, J162634.17-242328.7 (S1, #32), has been already investigated in several studies and is known to be a completely non-thermal source.…”
Section: Nature Of the Emission At 10 Ghzmentioning
confidence: 77%
See 2 more Smart Citations
“…The uncertainties correspond to the fit uncertainties only. The fluxes measured at 4.5 and 7.5 GHz come from Dzib et al (2013), while the ones at 107 GHz come from Kirk et al (2017). It should be noted that the The brightest source in our sample, J162634.17-242328.7 (S1, #32), has been already investigated in several studies and is known to be a completely non-thermal source.…”
Section: Nature Of the Emission At 10 Ghzmentioning
confidence: 77%
“…It was, however, detected at 5 GHz with the VLA at an angular resolution of ∼10 (measured peak fluxes of 130 -200 µJy beam −1 ; Leous et al 1991;Gagné et al 2004), although, in the first study, the source appears slightly offset by 3 . More recent ALMA observations suggest that SM1 is actually protostellar and that it hosts a warm (∼30-50 K) accretion disk or pseudo-disk (Friesen et al 2014;Kirk et al 2017;Friesen et al 2018).…”
Section: Source Census and Comparison With Other Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows that there is substantial extended emission between IRS 47 and ALMA J162729.7. Kirk et al (2017) weakly detected similar extended emission at 3 mm in ∼ 2 resolution ALMA data, and Kamazaki et al (2019) strongly detected this structure in 1.3 mm continuum, 13 CO (2-1), and C 18 O (2-1) in their ALMA observations that combine the 12 m main array and the compact ACA. The arc structure curves further around IRS 47 in the two line tracers, forming a near bubble and the arc also coincides with 70 µm emission from Herschel (Kamazaki et al 2019).…”
mentioning
confidence: 83%
“…The continuum source is well resolved, with a deconvolved size of 81 au × 37 au and a mass of 8 M Jupiter . Kirk et al (2017) found a much higher mass of 0.071 M (74 M Jupiter ) in lower resolution 3 mm observations, Figure A32. Same as Figure A1 except for VLA 1623A and VLA 1623B.…”
mentioning
confidence: 93%